Bright Blue and White Electrophosphorescent Triarylboryl‐Functionalized C^N‐Chelate Pt(II) Compounds: Impact of Intramolecular Hydrogen Bonds and Ancillary Ligands. (4th December 2013) - Wang, Xiang; Chang, Yi‐Lu; Lu, Jia‐Sheng; Zhang, T.; Lu, Zheng‐Hong; Wang, Suning
<x xml:space="preserve">Abstract</x> New blue and blue‐green phosphorescent C^N chelate Pt(II) compounds that contain a dimesitylboryl‐functionalized phenyl‐1, 2, 3‐triazole ligand (Bptrz) are synthesized. The influence of three different ancillary ligands, namely acetylacetonato (acac), picolinate (pic) and pyridyl‐1, 2, 4‐triazolyl (pytrz), on phosphorescence quantum efficiency and excimer emission is examined. Pt(II) compounds with a p‐Bptrz ligand consistently emit a blue‐green color with an emission wavelength = 490–500 nm while those with a m‐Bptrz ligand emit a blue color with λem = 450–460 nm and a quantum efficiency as high as 0.97. In addition to the blue monomer emission peak, Pt(m‐Bptrz)(pytrz) compounds display an excimer emission peak at ∼550 nm in a solid matrix whose intensity is dependent on the substituent group on pytrz and the doping concentration. As a result of the monomer and excimer emission, bright white phosphorescence is observed for several members of Pt(m‐Bptrz)(pytrz) compounds. Intramolecular CH···N hydrogen bonds are found to play an important role in the high stability and high phosphorescent quantum efficiency of Pt(m‐Bptrz)(pytrz) compounds. Single‐dopant blue and white electrophosphorescent devices using Pt(m‐Bptrz)(CF3‐pytrz‐Me) or Pt(m‐Bptrz)(t‐Bu‐pytrz‐Me) as the emitter are successfully fabricated. White electroluminesence devices with external quantum efficiency of 15.6% and CIE (xy) of 0.31, 0.44 are achieved.